Epigenetic dynamics during germline development: insights from Drosophila and C. elegans. - Gleason, R.J.; Chen, X. (Current Opinion in Genetics and Development, 2023)
Gametogenesis produces the only cell type within a metazoan that contributes both genetic and epigenetic information to the offspring. Extensive epigenetic dynamics are required to express or repress gene expression in a precise spatiotemporal manner. On the other hand, early embryos must be extensively reprogrammed as they begin a new life cycle, involving intergenerational epigenetic inheritance. Seminal work in both Drosophila and C. elegans has elucidated the role of various regulators of epigenetic inheritance, including (1) histones, (2) histone-modifying enzymes, and (3) small RNA-dependent epigenetic regulation in the maintenance of germline identity. This review highlights recent discoveries of epigenetic regulation during the stepwise changes of transcription and chromatin structure that takes place during germline stem cell self-renewal, maintenance of germline identity, and intergenerational epigenetic inheritance. Findings from these two species provide precedence and opportunity to extend relevant studies to vertebrates.